Have migrant remittances influenced self-employment and welfare among recipient households in Nigeria? - Salman, Kabir K. (International Food Policy Research Institute, 2016)
Despite a number of studies around the world focusing on the role of remittances in households’ livelihood, this topic has not been well documented in Nigeria. To fill this gap, this study examines the influence of remittances on self-employment status and welfare among recipient Nigerian households using data from Migration and Remittances Household Surveys conducted by the World Bank in 2009 and 2010. Results find that remittances decreased the probability of recipients being self-employed by 28.4 percent. In addition, per capita expenditures of recipient households were ₦80,695.25 (equivalent to USD 536.77) compared to ₦35,865.77 for non-recipient households; in other words, recipient households had 92.3 percent higher per capita expenditures than non-recipients. Based on these results, a public enlightenment campaign on the need to invest remittances, trainings to build households’ entrepreneurial skills, and supportive government business promotion policies are recommended. Full Paper